Rules a short history of what we live by - Daston, Lorraine (Oxford Princeton University Press, 2022)
Daston uncovers three enduring kinds of rules: the algorithms that calculate and measure, the laws that govern, and the models that teach. She vividly illustrates how rules can change―how supple rules stiffen, or vice versa, and how once bothersome regulations become everyday norms. Rules have been devised for almost every imaginable activity and range from meticulous regulations to the laws of nature. Daston probes beneath this variety to investigate when rules work and when they don?t, and why some philosophical problems about rules are as ancient as philosophy itself while others are as modern as calculating machines.
Includes index